Risk stratification in cardiac amyloidosis: novel approaches - Kristen, Arnt; Meyer, Franz Joachim; Dengler, Jolanta; Schönland, Stefan; Hundemer, Michael; Hegenbart, Ute; Singer, Reinhard; Schnabel, Philipp Albert; Sack, Falk-Udo; Goldschmidt, Hartmut; Katus, Hugo; Dengler, Thomas (Transplantation, 2005)
Amyloidosis is a term for diseases with extracellular deposition of insoluble beta-fibrillar proteins in different organs. The heart is primarily involved in more than half of patients with immunoglobulin light-chain amyloidosis or hereditary amyloidosis and associated with poor prognosis. Different traditional diagnostic tools that have been described for risk stratification lack of sufficient sensitivity and specificity for patient survival. Until November 2004 in 50 consecutive patients with light chain amyloidosis and 15 patients with hereditary amyloidosis electrocardiography, echocardiography, Holter monitoring, cardiopulmonary exercise test, lung function testing, tilt-test, and laboratory investigations have been performed at our department. Cardiac amyloidosis was found in 32 patients. Interventricular septum (14.3±0.5 mm vs. 12.3±0.7 mm, P<0.05), plasma NT-proBNP (7154±2122 ng/l vs. 380±113 ng/l; P<0.01), cardiac Troponin T (0.105±0.030 vs. 0.019±0.010 μg/l; P<0.05) were increased in patients with cardiac amyloidosis as compared to patients light chain amyloidosis but no cardiac involvement. Maximal inspiratory (Pimax) and expiratory (Pemax) mouth pressure were decreased with CA compared to controls. Correlation of NT-proBNP and interventricular septum thickness (r=0.53, P=0.029) as well as and Pimax (r=0.72, P<0.01) or Pemax (r=0.69; P<0.01) was noticed. A correlation of grade of arrhythmias in Holter monitoring and syncopes was not observed.Cardiac involvement of amyloid disease carries a poor prognosis and is not well characterized by classic heart failure determinants. Heart transplantation based on novel risk markers including NT-proBNP might be a suitable therapeutic approach for patients with manifest cardiac amyloidosis, but will require alternative patient selection and listing criteria.